2020
DOI: 10.1177/8756479320905816
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence the Communication of Adverse Findings in Obstetrics: A Survey of Current Sonographer Practices in Australia

Abstract: Objective: To identify factors influencing sonographers’ practices in communicating adverse obstetric findings and to understand their views on the need for standardized national policies and guidelines. Methods: Qualified and trainee sonographers who currently perform obstetric sonography were invited to complete a survey through the Australasian Sonographers Association. Closed-ended questions sought information on the demographic profile of the participants and their experiences on a range of issues related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…14 In addition to these qualitative studies, there have been a small number of recent quantitative survey studies in sonographers. 15,16,17 Consistent with findings from studies in expectant parents, these have suggested that sonographers believe a policy of immediate disclosure of findings is a feature of patient-centred care, 8,17 but that delivering news in this way is challenging when guidelines are unclear or support from other healthcare professionals is lacking. 15,16 There is a need for further qualitative research to better understand the experiences of UK sonographers in relation to news delivery for three main reasons.…”
Section: Introductionmentioning
confidence: 77%
“…14 In addition to these qualitative studies, there have been a small number of recent quantitative survey studies in sonographers. 15,16,17 Consistent with findings from studies in expectant parents, these have suggested that sonographers believe a policy of immediate disclosure of findings is a feature of patient-centred care, 8,17 but that delivering news in this way is challenging when guidelines are unclear or support from other healthcare professionals is lacking. 15,16 There is a need for further qualitative research to better understand the experiences of UK sonographers in relation to news delivery for three main reasons.…”
Section: Introductionmentioning
confidence: 77%
“…Within Australia, the responsibility of the communication of unexpected findings in obstetric ultrasound has increasingly, yet inconsistently, shifted to sonographers 21 . A survey of qualified obstetric sonographers and trainees found that 79 (31.7%) respondents had communicated a congenital anomaly finding to their pregnant patient within the preceding month 22 . Despite this frequency, 63.5% of workplaces did not have policies about the communication of unexpected findings, and only 35% of the respondents had undertaken specific training, most commonly after qualifying 22 …”
Section: Discussionmentioning
confidence: 99%
“…21 A survey of qualified obstetric sonographers and trainees found that 79 (31.7%) respondents had communicated a congenital anomaly finding to their pregnant patient within the preceding month. 22 Despite this frequency, 63.5% of workplaces did not have policies about the communication of unexpected findings, and only 35% of the respondents had undertaken specific training, most commonly after qualifying. 22 Expectant parents are often alluded to unexpected findings through the sonographers' body language and they have expressed a desire for immediate information.…”
Section: Challenges For Expectant Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,18 This creates difficulties for Australian sonographers as frontline practitioners as they do not have any formal authority or control in their interactions with pregnant patients and other healthcare professionals, such as referrers. Our research suggests it is challenging for a sonographer to provide patient-focused care 9,18,19 and put the needs of the mother first when they are prohibited from discussing findings with a pregnant patient.…”
Section: Sonographers In Australiamentioning
confidence: 99%